The role of the cross-link His-Tyr in the functional properties of the binuclear center in cytochrome c oxidase - Pinakoulaki, Eftychia; Pfitzner, Ute; Varotsis, Constantinos (My University, 2002)
Resonance Raman and Fourier transform infrared spectroscopies have been used to study the aa3-type cytochrome c oxidase and the Y280H mutant from Paracoccus denitrificans. The stability of the binuclear center in the absence of the Tyr280-HiS276 cross-link is not compromised since heme a3 retains the same proximal environment, spin, and coordination state as in the wild type enzyme in both the oxidized and reduced states. We observe two C-O modes in the Y280H mutant at 1966 and 1975 cm-1. The 1975 cm-1 mode is assigned to a γ-form and represents a structure of the active site in which CuB exerts a steric effect on the heme a3-bound CO. Therefore, the role of the cross-link is to fix CuB in a certain configuration and distance from heme a3, and not to allow histidine ligands to coordinate to CuB rather than to heme a3, rendering the enzyme inactive, as proposed recently (Das, T. K., Pecoraro, C., Tomson, F. L., Gennis, R. B., and Rousseau, D. L. (1998) Biochemistry 37, 14471-14476). The results provide solid evidence that in the Y280H mutant the catalytic site retains its active configuration that allows O2 binding to heme a3. Oxygenated intermediates are formed by mixing oxygen with the CO-bound mixed-valence wild type and Y280H enzymes with similar Soret maxima at 438 nm
Keywords: Biochemistry; Enzymes; Infrared spectroscopy; Resonance; Carbon; Copper; Cytochrome oxidase; Protein binding; Raman spectrometry